2018
DOI: 10.1364/oe.26.019665
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of single-shot damage of Ru thin films irradiated by femtosecond extreme UV free-electron laser

Abstract: Ruthenium is a perspective material to be used for XUV mirrors at free-electron laser facilities. Yet, it is still poorly studied in the context of ultrafast laser-matter interaction. In this work, we present single-shot damage studies of thin Ru films irradiated by femtosecond XUV free-electron laser pulses at FLASH. Ex-situ analysis of the damaged spots, performed by different types of microscopy, shows that the weakest detected damage is surface roughening. For higher fluences we observe ablation of Ru. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 56 publications
2
24
0
Order By: Relevance
“…If we assume that there is a damage threshold in the range of 20-25 mJ/cm 2 it will lead to the conclusion that with 209 pulses, the Ru film was exposed to a larger number of pulses that can cause damage than in the 1600 pulses case, explaining the larger damage with 209 pulses. In our recent investigations [7] we showed that the nature of single-shot XUV-induced ablation of Ru is photomechanical spallation in the stress confinement regime. The latter means that heating of the lattice is faster than the acoustic relaxation time, which means that heating occurs at almost isochoric conditions.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…If we assume that there is a damage threshold in the range of 20-25 mJ/cm 2 it will lead to the conclusion that with 209 pulses, the Ru film was exposed to a larger number of pulses that can cause damage than in the 1600 pulses case, explaining the larger damage with 209 pulses. In our recent investigations [7] we showed that the nature of single-shot XUV-induced ablation of Ru is photomechanical spallation in the stress confinement regime. The latter means that heating of the lattice is faster than the acoustic relaxation time, which means that heating occurs at almost isochoric conditions.…”
Section: Resultsmentioning
confidence: 97%
“…It was shown in damage studies of metals induced with optical lasers [18][19][20] that this situation leads to the generation of large thermo-induced stresses and, as a result, to spallation of the top part of a metal. The single-shot spallation threshold at 20 • grazing incidence was measured to be Fspall=64+/-13 mJ/cm 2 of absorbed fluence, while the melting threshold was calculated to be Fmelt=13 mJ/cm 2 [7]. It is known from literature [18], that spallation starts with nucleation of subsurface voids or cavities in a melted layer of irradiated metal, created as a result of propagation of a tensile stress wave.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively high value of its critical angle (27°at 92 eV photon energy) allows operation in a wide range of grazing incidence angles. In our recent study [13], we investigated femtosecond XUV-induced single-shot damage of a 50 nm thick Ru film on a Si substrate. The experiment was performed at Free-electron LASer in Hamburg (FLASH) [1].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental analysis of the damaged morphologies, together with simulations of photoabsorption and ultrafast evolution of electron and lattice temperatures, showed that the nature of single-shot damage is photomechanical spallation, a phenomenon that was previously studied in the case of irradiation of solids with optical [14][15][16][17][18][19] and XUV [20][21][22][23] lasers. The spallation threshold for Ru was measured to be F spal 200 40 mJ∕cm 2 of incident fluence [13].…”
Section: Introductionmentioning
confidence: 99%